Implementation of Ultra Micro Financing Based on DSN-MUI Fatwa Number 119 - Asmuni; Tartila, Muzayyana (Journal of Multi-Disciplines Science, 2023)
There are many problems in the Kecil community, namely the lowest level, AMD, and reversed financing. Ultra-Micro financing is here to provide solutions to the lower classes of society who need capital loans. This financing is regulated by Fatwa of the National Sharia Council No. 119/DSN-MUI/II/2018. This study aims to discover how the practices, mechanisms, and governance of ultra-micro financing follow sharia. The method used in this research is the empirical observation method and the literature research method. First, gather various reading sources, such as newspapers and articles. The study concluded that the channelling institution is an Islamic financial institution following DSN MUI Fatwa No 119/DSN-MUI/II/2018. The source of Super Micro Financing funds is the DSN MUI fatwa, the practice of unlawful interest. The source of Super Micro Financing funds is the DSN MUI fatwa, the method of unlawful interest. Determination of profit margins in the DSN MUI fatwa No 119/DSN-MUI/II/2018 uses the concept of profit sharing and is based on a predetermined contract. Supermicro Financing dispute resolution, according to DSN MUI fatwa No 119/DSN-MUI/II/2018, Dispute settlement is carried out through a Sharia-based dispute resolution institution.